2016
DOI: 10.5114/wo.2016.64596
|View full text |Cite
|
Sign up to set email alerts
|

Determining the potential of desmoglein 3 as a sensitive and specific immunohistochemical marker for the detection of micrometastasis in patients with primary oral squamous cell carcinoma

Abstract: Aim of the studyDespite advances in surgical and radiotherapy techniques, the presence of lymph node metastasis drastically decreases the survival rate of patients with primary oral squamous cell carcinoma (OSCC). Thus the accurate pathological staging of the neck is critical. Desmoglein 3 (DSG3), a desmosomal cadherin protein is said to be highly expressed in head and neck squamous cell carcinoma (HNSCC) and in metastatic cervical lymph nodes, but absent in non-invaded nodes. With an aim to improve the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Nagvekar et al . [ 25 ] also reported the presence of DSG3+ histiocytes in lymph node tissue and they confirmed the origin of these cells by immunostaining with CD 68 (pan macrophage marker) and CD163 (marker for M2 phenotype). The current study also found substantial number of macrophages in subcapsular sinuses, interfollicular areas, medullary sinuses as well as within the lymphoid follicles which stained positively with DSG3, which is a less reported but interesting finding [ Figure 3 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nagvekar et al . [ 25 ] also reported the presence of DSG3+ histiocytes in lymph node tissue and they confirmed the origin of these cells by immunostaining with CD 68 (pan macrophage marker) and CD163 (marker for M2 phenotype). The current study also found substantial number of macrophages in subcapsular sinuses, interfollicular areas, medullary sinuses as well as within the lymphoid follicles which stained positively with DSG3, which is a less reported but interesting finding [ Figure 3 ].…”
Section: Discussionmentioning
confidence: 80%
“…[ 21 ] Similar staining of dendritic cells with CK was observed in the current study. According to Nagvekar et al .,[ 25 ] these macrophages show positivity for both DSG3 and CK and this may be attributed to the presence of ingested processed antigens within these cells, before migration to lymph nodes. Thus, micrometastatic and macrometastatic deposits were easier to identify in comparison to ITC on staining with DSG3.…”
Section: Discussionmentioning
confidence: 99%